Development and Validation of a High-Throughput Quantification Method of Crown Procyanidins in Different Wines by UHPLC-Q-TOF - Manon Ferreira; Pierre-Louis Teissedre; Michaël Jourdes (Methods and Protocols)
Procyanidins are widely distributed in plant-derived foods, and consist of flavanol oligomers and polymers. Recently, the crown procyanidin sub-family, characterised by a unique macrocyclic structure, has been identified in grapes and wine. This study reports the development and validation of a rapid and quantitative analytical method measuring crown procyanidin concentration in red and white wines using ultra-high-performance liquid chromatography (UHPLC) coupled with a Q-TOF mass spectrometer. Validation followed international standards, demonstrating high sensitivity (LOQ = 0.033 mg/L), accuracy (recovery = 88.21% to 107.64%), repeatability (RSD = 1.99% to 11.03%), and intermediate reproducibility (RSD = 2.51% to 19.05%). Minimal matrix effects were observed, ensuring reliable and precise quantification across both wine types. The applicability of the method was confirmed through the successful analysis of wine samples, leading to the first quantification of crown procyanidins in white wine. Concentrations ranged from 0.81 mg/L to 15.88 mg/L in the different analysed wines. This validated method provides a valuable tool for the study of crown procyanidin profiles in various wine matrices and establishes a foundation for future research into the role of crown procyanidins in wines and other food and beverage matrices where these compounds may be present.